Safety and Efficacy of 48 and 96 Weeks of Alendronate in Children and Adolescents With Perinatal Human Immunodeficiency Virus Infection and Low Bone Mineral Density for Age. (25th June 2020) - Lindsey, Jane C; Jacobson, Denise L; Spiegel, Hans M; Gordon, Catherine M; Hazra, Rohan; Siberry, George K
Abstract: No safety concerns were identified in a randomized, crossover study of alendronate/placebo in youth with perinatal HIV infection and low bone mineral density (BMD). BMD improved with 48 weeks of alendronate and continued to improve with an additional 48 weeks of therapy. Gains were largely maintained 48 weeks after stopping alendronate.